Maresha. - Stern, Ian. (Jerusalem)
ix, 363 sayfa
Keywords: “This volume provides an archaeological study of 152 subterranean complexes at ancient Maresha, including an overview of the site, geological background, typological analysis of chamber types, and documentation of all surveyed installations. Two brief excavation reports offer insights into material culture and daily life during the Hellenistic period. Carved decorative elements—such as niches, altars, reliefs, and betyls—highlight religious diversity and cultural syncretism among Maresha’s residents. Twenty-one inscriptions, mostly Greek with three Semitic, provide rare direct evidence of the activities, identities, and experiences of individuals who used these underground spaces, adding a human dimension to the material findings. Special attention is given to the decline and decommissioning of certain complexes, shedding light on the evolving needs and priorities of the Maresha population. The synthesis examines changes in construction, abandonment, and reuse patterns over time within larger political and economic contexts, ending with a brief overview of Maresha after its conquest by John Hyrcanus I in 112 BCE“ --